Reproduction in domestic ruminants during the past 50 yr: discovery to application. (19th April 2018) - Smith, Michael F; Geisert, Rodney D; Parrish, John J
Abstract: The study of reproductive physiology in domestic ruminants has progressed from the whole animal to the molecular level in an amazingly short period of time. The volume of information on this subject is enormous; therefore, we have focused on domestic ruminants, with an emphasis on cattle. To date, artificial insemination (AI ) is perhaps the most powerful technique that reproductive physiologists and geneticists have provided the livestock industry for genetic improvement. Early efforts to establish AI as a tool were initiated in Russia around 1899 and since that time major advances in methods of semen collection, evaluation of male fertility, cryopreservation of sperm, sex-sorted semen, and estrous cycle control have occurred. The preceding advances not only led to the widespread use of AI, but also contributed to our fundamental understanding of ovulation control, timing of insemination, gamete biology, and cryopreservation. In regards to anestrus, our understanding of the concept of neuroendocrine control of the pituitary gland and the role of steroid feedback led to the Gonadostat Theory, which proposes that onset of puberty is due to a decrease in the negative feedback of gonadal steroids over time. Subsequent studies in prepuberal and postpartum sheep and cattle established that a short luteal phase frequently precedes the first normal length cycle that is accompanied by estrous expression. This observation led to the common practice of treating prepuberal heifers and anestrous postpartum cows with a short-term progestin treatment (e.g., Controlled Internal Drug Release) to induce normal estrous cycles. In domestic ruminants, fertilization rate is high (85% to 95%); however, significant embryonic mortality before or around the time of maternal recognition of pregnancy (MRP ) reduces the pregnancy rate to a single breeding. Significant effort has been directed at determining the time of MRP, the signal for MRP, as well as elucidating the physiological, cellular, and molecular dialogue between the conceptus and uterine environment. Advancements have now led us to the ability to edit the genome to alleviate disease and possibly improve production traits. In summary, major advancements in our understanding of reproductive biology have stemmed from efforts to establish the AI and embryo transfer technique and reduce the negative impact of anestrus and embryonic mortality in domestic ruminants.